Diseño de un sistema de costos para mejorar la productividad en la Empresa Textil Safiara Jeans, parroquia Bolívar, cantón Pelileo, provincia Tungurahua, año 2018. - Cunalata Iza, Viviana Maricela (2019)
This research work is developed in order to identify, classify, and control the costs in the textile company Safiara Jeans, which is dedicated to the manufacture of jeans, with the purpose that the raw material, labor and costs are used. Indirect that is required for each order, thus avoiding the waste of materials, economic losses and low liquidity. The company, having no knowledge about costs, does not take into account its elements; as the indirect costs of manufacturing, nor the labor of the husband and the owner in the production, distribution and sale phases, obtaining as a result an over utility. The methodology used for the realization of the present project includes the field investigation, since the information was collected, observation, use of interview to the owner and surveys to the personnel of the company, to have this information analyzed in a way systematic and deep, the results obtained were that the company does not have a cost system to control its activities. For this reason a comparative study of the different costing systems was carried out, using bibliographic research in order to have clear knowledge of each of these systems, where it was possible to define that a cost system for production orders is the more suitable and easy to handle for the company, it should also be emphasized that the costs of the products are made empirically and according to the competitiveness that exists in the market. Therefore, a proposal is generated to raise a cost system for production orders to improve productivity and profitability thus providing greater benefits to its owner and workers, determining the real unit cost of jeans $ 9.72. Keywords: system, costs, production, profitability, sale price